Direkam di sekolah, Sweet Seventeen, KTP-el ku Datang: Inovasi Pemerintah Kota Surakarta - Ria, Damai; Adnan, Muhammad (Journal of Politic and Government Studies, 2019)
E-KTP innovation is a method of improving optimal public services, noting that innovation can renew ineffective systems, especially in the field of civil registration. In optimal public service, community response is also important in the accountability of a public policy. This is stated in the example of the E-KTP innovation policy in Surakarta, namely